2019
DOI: 10.1021/acsami.9b03745
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Doped Carbon Nitrides with Accelerated Interfacial Charge/Mass Transportation for Boosting Photocatalytic Hydrogen Evolution

Abstract: The interaction of water molecule with catalysts is crucial to photocatalysis, but the surface property manipulation still remains a great challenge. In this study, we report an in situ multiple heteroelement (sodium, oxygen, and iodide) doping strategy based on a molten salt-assisted route to prepare a green-colored carbon nitride (GCN). The as-prepared GCN yields 25.5 times higher H 2 evolution rate than that of bulk polymeric carbon nitride under visible light. Experimental characterization data demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…10,11 There are several ways to intercalate Na + or K + into GCN including the calcination of a mixture of carbon nitride precursors (cyanamide, melamine, etc.) with alkali halide, [11][12][13][14][15][16][17][18][19][20][21][22] a mixture of the prepared GCN and alkali halide, [23][24][25][26][27] a mixture of carbon nitride precursors and alkali metal hydroxide, [28][29][30][31] and a mixture of the prepared GCN and alkali metal hydroxide. 6,[32][33][34][35] Most of the studies revealed that for one or several factors, alkali metal ion doping in GCN can help increase its surface specic area, 6,11,19,20,23,29 promote its crystallinity, 15,17,22,27 enhance its light absorption, 13,[15][16][17]19,21,22,27 reduce its bandgap,…”
Section: Introductionmentioning
confidence: 99%
“…10,11 There are several ways to intercalate Na + or K + into GCN including the calcination of a mixture of carbon nitride precursors (cyanamide, melamine, etc.) with alkali halide, [11][12][13][14][15][16][17][18][19][20][21][22] a mixture of the prepared GCN and alkali halide, [23][24][25][26][27] a mixture of carbon nitride precursors and alkali metal hydroxide, [28][29][30][31] and a mixture of the prepared GCN and alkali metal hydroxide. 6,[32][33][34][35] Most of the studies revealed that for one or several factors, alkali metal ion doping in GCN can help increase its surface specic area, 6,11,19,20,23,29 promote its crystallinity, 15,17,22,27 enhance its light absorption, 13,[15][16][17]19,21,22,27 reduce its bandgap,…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Shi et al prepared a green-colored carbon nitride (GCN) with enhanced H 2 evolution through an in situ multiple heteroelement doping strategy (Figure 9a). [58] Under visible light, the as-prepared GCN exhibited 25.5 times higher HER performance as well as excellent rhodamine B degradation activity in comparison with bulk polymeric carbon nitride (BCN) (Figure 9b,c). Results demonstrated that the significant increased photocatalytic activity was mainly due to the greatly enhanced hydrophilicity/aerophobicity, which accelerated the hydrogen liberation from the surface as well as the charge transfer (Figure 9a).…”
Section: Photocatalytic Reactionmentioning
confidence: 99%
“…[65] Designing highly active and stable electrocatalysts with superaerophobic surface and unique nanostructures is critical to enhancing the OER efficiency. Among various catalysts, such as NiFe layered double hydroxide (LDH) film, [66] amorphous NiCo hydroxide nanodendrite forests, [67] Co-doped SnS 2 nanosheet array, [68] metal@metal-oxide [58] Copyright 2019, American Chemical Society.…”
Section: Oxygen Evolution Reactionsmentioning
confidence: 99%
“…[ 46,48,55 ] In addition to alkali metal doping, MSM can realize the doping of other metals by changing the type of salt. Fang et al [ 83 ] prepared a green polycarbonitride by thermal polymerization of dicyandiamide and excess sodium iodide (Figure 7b). The experimental results showed that with the addition of sodium, oxygen and iodine, the conduction band of the catalyst moved negatively, the specific surface area increased, and the hydrophilicity enhanced.…”
Section: Advantages Of Msm For Photocatalyst Synthesismentioning
confidence: 99%
“…Reproduced with permission. [ 83 ] Copyright 2019, American Chemical Society. c–e) Characterization of the Co‐mCN.…”
Section: Advantages Of Msm For Photocatalyst Synthesismentioning
confidence: 99%